TESTICULAR CANCER IN SOETOMO HOSPITAL SURABAYA: RETROSPECTIVE STUDY - Mukti, Ade Indra; Hakim, Lukman; Djatisoesanto, Wahjoe; Hardjowijoto, Sunaryo (Indonesian Journal of Urology, 2018)
Objective: The aim of this study was to determine the characteristics of the testicular cancer that were managed in Soetomo Hospital. Materials & Methods: This was a retrospective descriptive study. We reviewed the medical records of patient with testicular tumor admitted in Soetomo Teaching Hospital Surabaya, from January 2008 until December 2013. The data regarding demographic characteristics, clinical presentation, grading and staging based on pathological examination result, and the management of the cancer. Data was presented in tabular and narrative in order to know the number and percentage of testicular cancer in Surabaya. Results: There were 46 patients with testicular cancer with mean age of 27.1 ± 7.9 years. Peak incidence was 15–35 years old (54%). Testicular mass was the most frequent clinical presentation in 42 patients (91%), abdominal mass and other complaints in 4 patients (9%). Most of the patients live outside Surabaya in 34 patients (72%). Location of the tumor was more frequently in scrotum, which occured in 42 patients (91%). A total of 4 patients (9%) were found to have a history of UDT. Based on the TNM staging, patients with stage pT3 were as many as 20 patients (43%), pT4 11 patients (24%), pT2 7 patients (15%) and pT1 4 patients (9%). In regional lymph nodes staging (N) N3 were as many as 26 patients (57%), N0 9 patients (20%), N2 5 patients (11%) and N1 2 patients (4%). Metastase staging (M) M0 was found in 27 patients (58%) and M1 tumor was found 42%. The major pathological finding was seminoma in 37 patients (80%), Yolk sac tumor in 4 patients (9%), Embryonal Ca in 1 patient (2%), Teratoma in 1 patient (2%) and mixed germ cell tumor in 3 patients (7%). The most widely theraphy was underwent orchidectomy followed by PEB chemotheraphy in 29 patients (64%), 3 patients (6%) underwent EBRT and PEB chemotheraphy, 5 patients (11%) underwent PEB chemotheraphy, There were 9 patients (19%) underwent orchidectomy alone. Group of seminoma tumor show normal limit of tumor marker α-FP and β-HCG and increased in non seminoma. Conclusion: Testicular cancer mostly appears in younger males. Most of testicular cancer was seminoma, diagnosed in advanced stage with metastase 42% of the patient. Most of the patients received orchidectomy followed by PEB chemotheraphy.